EFFECT OF SERVICE QUALITY ON INPATIENT SATISFACTION AT DR. SAIFUL ANWAR REGIONAL GENERAL HOSPITAL, EAST JAVA PROVINCE - Laili, Nurul; Hariyanti, Tita; Setijowati, Nanik (Journal of Community Health and Preventive Medicine, 2025)
This study aimed to analyze the effect of service quality on inpatient satisfaction at Dr. Saiful Anwar Hospital. This study was conducted using a quantitative method, and data were collected through questionnaires from 204 inpatients selected using probability sampling techniques. The results showed that the tangibles, assurance, and empathy dimensions had a positive and significant effect on patient satisfaction, which indicates that improvements in these areas lead to higher satisfaction levels. In contrast, reliability and responsiveness had a positive but not statistically significant effect on patient satisfaction, thus improvements in these areas may lead to increased satisfaction, although the impact is not statistically significant. Among the five dimensions, assurance emerged as the most dominant factor influencing inpatient satisfaction. As the study identified assurance as the dominant factor influencing patient satisfaction, Dr. Saiful Anwar Hospital is expected to improve patient safety assurance. One potential initiative is the implementation of a QR-based medical record system to streamline access to patient information and minimize the risk of human error.